Genome-Wide Identification, Evolution, and Expression Analysis of LBD Transcription Factor Family in Bread Wheat (Triticum aestivum L.) - Wang, Zhenyu; Zhang, Ruoyu; Cheng, Yue; Lei, Pengzheng; Song, Weining; Zheng, Weijun; Nie, Xiaojun (Frontiers in Plant Science, 2021)
The lateral organ boundaries domain (LBD) genes as the plant-specific transcription factor family, play the crucial role in controlling plant architecture as well as stress tolerance. Although it has been thoroughly characterized in many species, LBD family was not well studied in wheat. Here, the wheat LBD family was systematically investigated through an in silico genome-wide search method. Totally, 90 wheat LBD genes (TaLBDs) were identified, which were classified into Class I containing 7 subfamilies, and Class II including 2 subfamilies. Exon-intron structure, conserved protein motif and cis-regulatory elements analysis showed that the members in the same subfamily shared similar gene structure organizations, supporting the classification. Furthermore, the expression patterns of these TaLBD genes in different tissues as well as under diverse stresses were identified through public RNA-seq data analysis and the regulation networks of TaLBDs involved in were predicted. Finally, the expression levels of 12 TaLBDs were validated by QPCR analysis and the homoeologous genes showed differential expression. Additionally, the genetic diversity of TaLBDs in landrace population showed slightly higher than that of genetically improved germplasm population while obvious asymmetry at subgenome level. This study not only provided the potential targets for further functional analysis, but also contributed to better understand the roles of LBD genes playing in regulating development and stress tolerance in wheat and beyond.